SUPPLY CHAIN MANAGEMENT LPG 3KG IN INDONESIA - Grace Kezia Anang (AIBPM Publisher, 2018)
The Indonesian Government employs a policy of subsidizing household cooking energy. The annual subsidy for this energy reached 2.5 billion (all monetary amounts are in US dollars) in 2006 and the amount of subsidy has increased every year sincE (Budya, H: 2009). The traditional fuel for household cooking was kerosene. Its increasing price caused an increase in the amount of subsidy. The procurement, management, and distribution of the subsidized kerosene was outsourced to a government-owned oil company, Pertamina (csiro, et al: 2007) . This company has enjoyed monopoly rights since it was established. The government’s intention in granting the monopoly was to regulate and protect the market and people’s welfare. The regulation is implemented through price control of the kerosene retail price. The amount of subsidy was set at 85 cents per litre. During the last five years, the subsidy has drained the government budget. To reduce the amount of subsidy, the government initiated in 2007 a conversion of household cooking fuel to LP-gas (known locally as Elpiji) this gas is also known as propane or LPG (Akbar w: 2009). The reduction of subsidy that was expected from the conversion to LPG was estimated to be 1.7 billion annually. Recently, supply chain management has played an important role in enabling businesses to succeed in their goals, gain competitive advantage, and improve their performance. As a result, there has been extensive research into strategic supply chain management with the aim of improving business performance along each stage of the supply chain. This is because in the current business world, supply chain relationships are crucial in influencing many companies to continuously adopt proper supply chain management practices. However, there has been no attempt to study the impact of the supply chain relationships involving trust, commitment, strategic supplier partnerships and customer relationships management of the LPG supply chain in Indonesia.